WGP Congress 2014 - Merklein, Marion; Franke, Jörg; Hagenah, Hinnerk (Trans Tech Publications, 2014)
Collection of Selected, Peer Reviewed Papers from the 2014 WGP Congress, , September 9-10, 2014, Erlangen, Germany. The 76 Papers are Grouped as Follows: Keynotes, Chapter 1: Assembly, Chapter 2: Cutting and Grinding, Chapter 3: Forming, Chapter 4: Machines, Chapter 5: Organisati
Keywords: Cutting; Forming; Grinding; Production Assembly; Production Machines; Production Organisation